Round Cell Tumors - Classification & Overview - Kush Pathak; Prachi Nayak; Asha Karadwal; Sushruth Nayak; Satyajit Tekade (Indian Journal of Forensic Medicine & Toxicology, 2021)
Round cell tumors from time indefinite have been affecting mankind, not only by their dangerous and lifethreatening nature but also by their vast variety. Number of tumors share similar histology, composed ofrelatively uniform primitive Small Round Blue Cells. They also share many demographic, radiographicand clinical similarities, which often lead to misinterpretation and wrong diagnosis. These tumors, althoughsharing similar looks which is quite confusing, come from different origin, in different sizes, colors, site ofaction & most importantly nature. A few are aggressive and others are latent and benign. In some cases theetiology is known, however on the other hand a large number of these tumors have an idiopathic etiology.Whatever the lesion or however the appearance clinically, histopatholgically or cytologically, these round celltumors, continue to fascinate and confuse us & lack of a proper classification adds to the misinterpretation.This review article is thus an attempt to go through this vast variety of tumor thoroughly along with anattempt to provide a proper classification for the tumor itself.